Pharmacologically Distinct Nicotinic Acetylcholine Receptors Drive Efferent-Mediated Excitation in Calyx-Bearing Vestibular Afferents - Holt, J. Chris (J Neurosci, 2015)
Electrical stimulation of vestibular efferent neurons rapidly excites the resting discharge of calyx/dimorphic (CD) afferents. In turtle, this excitation arises when acetylcholine (ACh), released from efferent terminals, directly depolarizes calyceal endings by activating nicotinic ACh receptors (nAChRs). Although molecular biological data from the peripheral vestibular system implicate most of the known nAChR subunits, specific information about those contributing to efferent-mediated excitation of CD afferents is lacking. We sought to identify the nAChR subunits that underlie the rapid excitation of CD afferents and whether they differ from α9α10 nAChRs on type II hair cells that drive efferent-mediated inhibition in adjacent bouton afferents. We recorded from CD and bouton afferents innervating the turtle posterior crista during electrical stimulation of vestibular efferents while applying several subtype-selective nAChR agonists and antagonists. The α9α10 nAChR antagonists, α-bungarotoxin and α-conotoxin RgIA, blocked efferent-mediated inhibition in bouton afferents while leaving efferent-mediated excitation in CD units largely intact. Conversely, 5-iodo-A-85380, sazetidine-A, varenicline, α-conotoxin MII, and bPiDDB (N,N-dodecane-1,12-diyl-bis-3-picolinium dibromide) blocked efferent-mediated excitation in CD afferents without affecting efferent-mediated inhibition in bouton afferents. This pharmacological profile suggested that calyceal nAChRs contain α6 and β2, but not α9, nAChR subunits. Selective blockade of efferent-mediated excitation in CD afferents distinguished dimorphic from calyx afferents by revealing type II hair cell input. Dimorphic afferents differed in having higher mean discharge rates and a mean efferent-mediated excitation that was smaller in amplitude yet longer in duration. Molecular biological data demonstrated the expression of α9 in turtle hair cells and α4 and β2 in associated vestibular ganglia.